THE RELATIONSHIP OF THESIS GUIDANCE THROUGH ONLINE MEDIA WITH STRESS LEVEL OF NURSING STUDENTS - Herwinda Sinaga (Jurnal Vokasi Keperawatan (JVK), 2021)
Stress is a body response that is not specific to problems or burdens, feelings of discomfort, or pressure, both physical and psychological as an individual response, online guidance that is felt to lack interaction between lecturers and students can form a learning process. This study aims to see the relationship between thesis guidance through online media and the level of stress of the eighth semester nursing students at the Immanuel College of Health, Bandung. This research is a type of quantitative research that uses a cross sectional approach. The sample in this study may be 42 respondents using total sampling technique. The instrument used was a questionnaire instrument to measure stress levels using DASS 42 and online guidance using a closed questionnaire. The results of the analysis of this study using the Spearman Rank test indicate that there is a relationship between thesis guidance through online media with the stress level of semester VIII nursing students at Immanuel College of Health Sciences Bandung (p-value 0.000 <0.05). Suggestions are expected to align online and offline thesis guidance activities carried out by lecturers with the distribution of the proportions, so that it can make it easier for lecturers to evaluate students' understanding of the preparation of final study assignments (Thesis) and can reduce stress that has a negative impact on students.